A Study on the Influence of the Conglomerate Mesostructure on Fracture Failure Behavior Based on Discrete Element Method. (27th January 2021) - Yan, Yu; Li, Shiyuan
Abstract : Rich in valuable reserves, conglomerate reservoirs in China have gradually emerged as a fundamental development source. Currently, research pertaining to the macromechanical properties of crack propagation in conglomerates is conducted either by directly employing various physical tests or by formulating a simplified numerical model for simulation, while disregarding the influence of the conglomerate mesostructure. In this paper, the analysis is performed by adopting techniques such as CT scanning and Particle Flow Code (PFC) numerical simulation. CT scanning is used to identify the mesoscopic structure of the conglomerate, and then, a numerical model is devised in accordance with the CT scanned digital image. Three-point bending simulation experiments are conducted for 3 sets of semicircular conglomerate specimens possessing prefabricated cracks, to analyze the influence of the initiation and evolution of mesostructure on the fracture failure behavior. Research suggests: ① The mesostructure within the conglomerate is complexified due to the presence of gravel. Conglomerate specimens exhibiting different mesostructures tend to diversify the possible modes of destruction of the conglomerate. ② A fluctuation is noticed at peak load under the fracture toughness test. The numerical simulation of the fracture toughness undertaken via the PFC method revealed the reason for the peak load fluctuation during the fracture propagation to be the constant penetration of the cracks into or out of gravel particles. ③ The fracture toughness simulation tests ascertain the existence of certain fracture characteristic units during the fracture propagation process, wherein the evolution of the internal mesostructure considerably influences the macroscopic failure mode of the conglomerate.